Critical Metals Mineralization in the Late-Stage Intrusions of Salmi Batholith, Ladoga Karelia, Russia - Vasily I. Ivashchenko (Minerals, 2023)
The paper reports the results of studies on critical metal mineralization genetically related to the late-stage intrusions of Salmi anorthosite-rapakivi granite batholith (SARGB) in the Riphean age. In, Bi, and Be mineralization in skarn-greisen deposits and occurrences at the SARGB endocontact, as well as REE and Nb-Ta mineralization in Li-F granites, understood as the late intrusive phases of the batholith, were studied. It is the first report on columbite-group minerals, as well as REE-Ta-Nb and REE mineralization in SARGB granites. Optical and scanning electron microscopy, EDS and LA ICP MS microanalysis, X-ray fluorescence spectrometry, Raman spectroscopy, and inductively coupled plasma mass spectrometry (ICP-MS) were used. The data obtained show that roquesite formation was mainly triggered by the decay of In-bearing solid sphalerite and chalcopyrite solutions. Zavaritskite, associated with unoxidized sulphides, was derived hypogenically and seldom occurs in ores. A helvine-group mineral association with zinc-enriched spinel (ZnO 22%–25%) seems to have been one of the factors preventing genthelvite formation. The Muzilampi, Hepaoja and Avtodor ore occurrences in Li-F granites display similar REE and Nb-Ta mineralization. They are associated with Y-fluorite and Li-siderophyllite, which contain exceptionally high Nb concentrations (0.25%–0.78%) in Muzilampi granites. Additionally, fluorite-1 is commonly overfilled (to >50%) with micron-sized synchisite and parisite inclusions. Columbite-tantalite-group minerals, present at all the occurrences studied, occur solely as ferricolumbites with a dominant Mn/(Mn + Fe) ratio of <0.2. Biotite and Li-siderophyllite, associated with columbite, have an extremely high iron index Fe/(Fe + Mg) > 0.9 approaching the maximum values (~1.0) in the most differentiated granites.